IMPROVING STUDENTSâ€™ SPEAKING SKILLS THROUGH THINK-PAIR-SHARE TECHNIQUE - Yanti, Melli; Rufinus, Albert; ., Regina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: Think-pair-share technique is a cooperative technique which is used to teach in the classroom with emphasized on activities students done at each of the stages. The purpose of this research was to describe how TPS technique improve studentsâ€™ speaking skill on the Eleventh grade students AP1 (Akomodasi Perhotelan) of SMKN 5 Pontianak. This research used classroom action research as the research design. The sample of this research were 28 students of Eleventh grade, Akomodasi Perhotelan class. There was improvement in each cycle after applying TPS technique in the classroom. The studentsâ€™ achievement in the first cycle was categorized as poor to average and studentsâ€™ achievement in the second and third cycle were categorized as average to good. The improvement also can be seen by the activeness of studentsâ€™ involvement in the speaking activities while teaching learning process. TPS technique can be used by the teacher as alternative to improve studentsâ€™ speaking skill. Â Â Keywords: Speaking skill, TPS technique, CARÂ Â Abstrak: Think-pair-share tehnik adalah tehnik kooperatif yang digunakan untuk mengajar dikelas yang menekankan pada aktifitas yang siswa lakukan disetiap langkah-langkahnya. Tujuan dari penelitian ini adalah untuk mendeskripsikan bagaimana tehnik TPS meningkatkan kemampuan berbicara siswa kelas 11 AP1 (Akomodasi Perhotelan) SMKN 5 Pontianak. Penelitian ini menggunakan penelitian tindakan kelas sebagai bentuk penelitian. Sampel dari penelitian ini adalah 28 siswa kelas 11 AP1 (Akomodasi Perhotelan). Terdapat peningkatan pada setiap siklusnya setelah penerapan tehnik TPS dikelas. Pencapaian siswa disiklus pertama dikategorikan â€œpoor to averageâ€ dan disiklus kedua dan ketiga dikategorikan â€œaverage to goodâ€. Peningkatan tersebut juga dapat dilihat melalui keaktifan dari keterlibatan siswa didalam aktifitas berbicara ketika proses belajar mengajar. Tehnik TPS bisa digunakan oleh guru sebagai alternatif untuk meningkatkan kemampuan berbicara siswa.Â Â Kata kunci: Kemampuan berbicara, tehnik TPS, CAR